PEMBERDAYAAN PEBISNIS UMKM DALAM PENENTUAN HARGA POKOKPRODUK, PERENCANAAN LABA DAN PENINGKATAN OMSET PENJUALAN - Muhammad Nuryatno Amin; Christina Dwi Astuti; Erie Riza Nugraha (Konferensi Nasional Pengabdian Masyarakat (KOPEMAS) #5 2024, 2020)
Phenomena shows that the entrepreneurs of the Micro, Small, and Medium Enterprises (MSME) faced some constraints in product costing, profit planning, and increasing sales. Even the all of the three aspects are critical success factors for the business. The aims of this activity are that the entrepreneurs of the MSME could be able to understand product costing, profit planning, and increasing sales. Due to in the pandemic era of Covid-19, this activity was carried out in terms of training delivered by webinar. Training materials consist of product costing, profit planning, and increasing sales. The participants were the MSME entrepreneurs from around of Indonesia. The effectivity of the training is measured by their perception related to their understanding to the materials delivered. Data collected by questionaires. Results shows that according to the the participats, this activity effectively reached their aims. It means that the training materials could be understand well by the participants. It is reccommended to monitor the enterpreneurs of the MSME in implementing the materials in order to make them well prepared to operate in the new normal era.